Sensory cell fates: four defaults for the price of one. - Wernet, M.F.; Desplan, C. (Current Biology, 2013)
The specification of different subtypes of olfactory sensilla, which harbor the olfactory receptor neurons (ORNs) in the Drosophila antennae, is poorly understood. Loss of the transcription factor Rotund (Rn) leads to a simultaneous mis-specification of several ORN classes, transforming them into different 'default' cell fates.